Influence of sex on the exposure to isoniazid in patients with pulmonary tuberculosis - Rivera, Juan Gonzalo Bardalez (2023)
Isoniazid is a key component of tuberculosis treatment. Adequate exposure is a determinant for therapeutic success; however, considerable inter- and intraindividual variations in drug plasma levels can lead to unfavorable outcomes. While some predictors of isoniazid levels are well-known, others, such as sex, yield controversial results, requiring further investigation to optimize exposure. This study investigates whether the sex of patients influences the dose administered and the concentrations of isoniazid in plasma. Levels of isoniazid were associated with the N-acetyltransferase 2 phenotypes. A total of 76 male and 58 female patients were included. Isoniazid was measured by high-performance liquid chromatography, and N-acetyltransferase 2 phenotypes were assessed using molecular techniques. The results show that the dose administered, expressed in mg/kg, was higher in females, but the plasma levels were similar between both sexes. Among patients, 46.2%, 38.8%, and 15% were slow, intermediate, and fast acetylators, respectively. As expected, isoniazid levels were associated with the acetylation phenotypes, with higher concentrations in the slow acetylators. Thus, sex-related difference in isoniazid levels is due to the body weight of patients, and the optimized dose regimen based on patient weight and acetylator phenotypes can improve the treatment outcomes.